Relentless reformer : Josephine Roche and progressivism in twentieth-century America - Muncy, Robyn (Politics and society in twentieth-century America., 2015)
Josephine Roche (1886-1976) was a progressive activist, New Deal policymaker, and businesswoman. As a pro-labor and feminist member of Franklin D. Roosevelt's administration, she shaped the founding legislation of the U.S. welfare state and generated the national conversation about health-care policy that Americans are still having today. In this gripping biography, Robyn Muncy offers Roche's persistent progressivism as evidence for surprising continuities among the Progressive Era, the New Deal, and the Great Society. Muncy explains that Roche became the second-highest-ranking woman in the New Deal government after running a Colorado coal company in partnership with coal miners themselves.